Ownership of English in the Outer and Expanding Circles: teachers' attitudes toward pronunciation in ESL/EFL teaching contexts. Issue 2 (4th May 2019) - Monfared, Abbas
ABSTRACT: In spite of the pluralistic view of English, the status of new Englishes is still largely considered controversial, and the presence of many varieties of English has important ramifications for teaching and assessment. This article examines the attitudes of 240 Outer Circle (OC) and Expanding Circle (EC) English teachers' awareness of and attitudes toward pronunciation in English as a second language/ English as a foreign language teaching contexts and how they respond to the proposal of a World Englishes approach in their teaching practice. The article showcases deeply rooted favo ritism toward American English among EC teachers and British English among OC teachers, and illustrates how relevant challenges arising from these attitudes can be addressed to meet the changing needs of future participants in international contexts. This article aims to contribute to the field of World Englishes, where studies relating to the OC and EC contexts are largely limited.